Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1097/00004010-200604000-00007
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Job Design in Long-Term Care Facilities and its Effect on Nursing Employee Satisfaction

Abstract: This study used quantitative and qualitative methods to examine the design of nursing jobs in long-term care facilities and the effect of job design on employee satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Observations previously conducted, as part of a larger study (Tyler et al, 2006), were used to categorise 20 long-term care facilities by teamwork amount: high, moderate, or low. After all facilities were categorised, all moderate-teamwork facilities were dropped from the sample leaving four high-teamwork and five low-teamwork facilities for analysis.…”
Section: Site Selectionmentioning
confidence: 99%
“…Observations previously conducted, as part of a larger study (Tyler et al, 2006), were used to categorise 20 long-term care facilities by teamwork amount: high, moderate, or low. After all facilities were categorised, all moderate-teamwork facilities were dropped from the sample leaving four high-teamwork and five low-teamwork facilities for analysis.…”
Section: Site Selectionmentioning
confidence: 99%
“…Such administrative tasks are often perceived as not directly relating to care and as preventing nurses from interacting with their patients (Tyler et al . ). In this evolving context, what qualifies as ‘administrative work’, its relationship to the wider nursing role and where/when/why it is considered a ‘burden’ remains insufficiently explored (Allen ).…”
Section: Introductionmentioning
confidence: 97%
“…In one study of job satisfaction among CNAs in nursing homes, Castle (2007) found that CNAs were satisfied working with residents but less satisfied with their pay and workload. Findings from a study conducted in eastern Massachusetts nursing homes indicated that CNAs were more satisfied with their work in nursing homes than licensed nurses (Tyler et al, 2006). Still, studies on the linkage between job satisfaction and actual turnover among CNAs are sparse.…”
Section: Introductionmentioning
confidence: 99%